2021
DOI: 10.1002/agj2.20868
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic characteristics and nutritional value of cactus pear progenies

Abstract: Cactus is an important fodder in tropical semiarid, but recent insect pressure has devastated cactus crops. Breeding programs are developing cactus varieties resistant to cochineal scale (Dactylopius opuntiae Cockerell). The cactus V‐19 (Opuntia larreyi F.A.C. Weber ex J. M. Coult.) has demonstrated resistance to cochineal scale, however, no breeding effort has been attempted with this species. This study characterized the resistance of cactus V‐19 progenies to cochineal scale. Morphological, productive, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
(76 reference statements)
0
0
0
Order By: Relevance
“…Hays often vary from 4 to 20% [39]. Despite accessions and cladode maturity phases, CP in spineless forage cactus was extremely low in our results (<6%), which represents the lowest quality forage according to general forage quality standards for livestock diets [35]. However, low CP levels can be improved through nutrient management practices.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Hays often vary from 4 to 20% [39]. Despite accessions and cladode maturity phases, CP in spineless forage cactus was extremely low in our results (<6%), which represents the lowest quality forage according to general forage quality standards for livestock diets [35]. However, low CP levels can be improved through nutrient management practices.…”
Section: Resultsmentioning
confidence: 57%
“…Santos et al [33,34] found 12% and 11.9% MM in spineless forage cactus studies. An average cladode MM concentration (15.7%) was reported by Garcia et al [35]. Spineless forage cactus frequently recorded high mineral concentrations attributed to the necessity for stomatal regulation and other physiological processes [36,37].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation